2016
DOI: 10.1016/j.arabjc.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on the structure of thiazolidine-2,4-dione and its 5-substituted derivatives in the gas phase. Implications for the thiazolidine-2,4-dione -water complex

Abstract: The results of a detailed DFT (B3LYP) investigation on five tautomers of thiazolidine-2,4-dione and their 5-substituted derivatives (ACH 3 , ANH 2 , ACl, AF, ACN-and NO 2 ) are presented here. The energy, geometrical parameters, topological parameters of all species in the gas phase have been calculated at B3LYP6-311++G(3df,2p)//B3LYP/311 + G(d,p) level of theory. The proton affinities (Pas), molecular electrostatic potential (MEP), natural valence atomic orbital energies (NNAO) of the basic center exist in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The diketo form shown in Figure a is the most stable form, and the relative stabilities of the tautomers are given in Table S1a (Supporting Information). Both the crystallographic study and the theoretical investigation showed that the most stable and predominant form of TZD is the diketo form. , The calculated optimized geometrical parameters for the diketo form in the present study compare well with the available crystallographic experimental data and are shown in Table S1b. The HOMO–LUMO transition energy of TZD was calculated with time-dependent density functional theory (TD-DFT) method using the B3LYP functional with the aug-cc-pvdz basis set.…”
Section: Computational Detailssupporting
confidence: 76%
See 1 more Smart Citation
“…The diketo form shown in Figure a is the most stable form, and the relative stabilities of the tautomers are given in Table S1a (Supporting Information). Both the crystallographic study and the theoretical investigation showed that the most stable and predominant form of TZD is the diketo form. , The calculated optimized geometrical parameters for the diketo form in the present study compare well with the available crystallographic experimental data and are shown in Table S1b. The HOMO–LUMO transition energy of TZD was calculated with time-dependent density functional theory (TD-DFT) method using the B3LYP functional with the aug-cc-pvdz basis set.…”
Section: Computational Detailssupporting
confidence: 76%
“…TZD exists in five tautomeric forms: thiazolidine (diketo), thiazoline (oxo-enol), and thiazole (dienol). , The optimized geometries of all the tautomeric forms were calculated and are shown in Figure . The diketo form shown in Figure a is the most stable form, and the relative stabilities of the tautomers are given in Table S1a (Supporting Information).…”
Section: Computational Detailsmentioning
confidence: 99%
“…In most cases, hydrogen transfer is the main reason for the keto-enol formation. The keto-enol are formed also in heterocyclic compounds containing the carbonyl group with acidic methylene protons connected to the heteroatom or to electro-withdrawing species, such as thiazolidine-2,4-dione [ 25 ], phenacyl bezoyl pyridinium [ 26 ], and 2-phenacyl benzoxazoles [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In systems with multiple sites of the same basic element type, the most basic site has the most negative MEP value, indicating a stronger molecular basicity. This understanding is essential for understanding proton affinity and gas-phase basicity 66 , 67 .…”
Section: Resultsmentioning
confidence: 99%